Workshop on Canva-Based Learning Media Design for Elementary School Teachers in Ladongi District - Rini Putri; Anas A; Bima B; Susan Safa Januari4; Nadira Almayasari; Asti Rahmawati; Putri Erwanda; Enjel E; Tri Wahyu Ningsih; Dimas Dwi Purnama; Apdal A; Muh. Reinal R (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service activity aims to improve the skills of elementary school teachers in Ladongi District in designing creative and effective digital learning media using the Canva platform. The main problem faced by teachers has been their limited ability to produce engaging, interactive, and student-centered learning materials in the digital learning era. The workshop was conducted through face-to-face training, demonstrations, and periodic mentoring. A total of 25 teachers from SDN 1 Atula in Ladongi District, East Kolaka Regency, participated in this activity. The results indicate an improvement in teachers’ abilities to create interactive presentation materials, digital worksheets, and other visual learning content. Furthermore, participants were able to integrate the designed media into classroom learning activities. Therefore, this workshop had a positive impact on supporting teachers’ creativity and competencies, particularly at SDN 1 Atula, Ladongi District, East Kolaka Regency, and contributed to improving the quality of elementary education at the school.